2015
DOI: 10.1021/jp511805x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathways for Water Oxidation to Molecular Oxygen Mediated by Model Cobalt Oxide Dimer and Cubane Catalysts

Abstract: Hybrid density functional theory calculations have been employed to investigate the water oxidation reaction on model cobalt oxide dimer and cubane complexes. Electronic structure and energetics of these model compounds were thoroughly investigated. The thermodynamically lowest energy pathway on the dimer catalyst proceeds through a nucleophilic attack of a solvent water molecule to Co(V)-O radical moiety. The lowest energy pathway on the cubane catalyst involves a geminal coupling of Co(V)-O radical oxo group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 37 publications
4
75
1
Order By: Relevance
“…This unusually high oxidation state for cobalt is predicted to be favored over the [Co(III) 2 Co(IV) 2 ] state by several theoretical calculations; the oxidation state assignment is discussed in the following section. 30,32,33 The reactions described above are consistent with the DFT calculations by Siegbahn for water oxidation, which indicate that 1(O) − is unable to engage in O−O bond formation by reaction with water; however, the higher oxidation state of 1(O) should allow attack by water to produce the hydroperoxy species 1(OOH) − . 30 Peroxide intermediates for cobalt catalysts have been speculated to exist based on observations by the groups of Frei and Stahl.…”
Section: ■ Kinetics and Proposed Mechanismsupporting
confidence: 79%
See 1 more Smart Citation
“…This unusually high oxidation state for cobalt is predicted to be favored over the [Co(III) 2 Co(IV) 2 ] state by several theoretical calculations; the oxidation state assignment is discussed in the following section. 30,32,33 The reactions described above are consistent with the DFT calculations by Siegbahn for water oxidation, which indicate that 1(O) − is unable to engage in O−O bond formation by reaction with water; however, the higher oxidation state of 1(O) should allow attack by water to produce the hydroperoxy species 1(OOH) − . 30 Peroxide intermediates for cobalt catalysts have been speculated to exist based on observations by the groups of Frei and Stahl.…”
Section: ■ Kinetics and Proposed Mechanismsupporting
confidence: 79%
“…Quantitative measurement by an O 2 -sensing probe revealed a ∼75% yield of O 2 with respect to 1, though the yield is most likely higher since a nontrivial amount of unmeasured bubbles adhered to the wall of the flask ( Figure 3A). Mass spectrometric measurement of the head space confirmed the presence of 32 Figure 3B). High-resolution electrospray ionization mass spectrometry (ESI-MS) analysis of the solution after reaction with Na 18 OH showed no measurable incorporation of 18 …”
Section: ■ Electrochemistry and Reaction Chemistrymentioning
confidence: 85%
“…We did not consider a geminal coupling mechanism involving a bridging oxygen atom of the cubane cage as was suggested by Fernando and Aikens for a Co(III) cubane. 34 The reasoning for this is that while their model cubane only had water ligands bound to the Co centers, in 1, the bridging oxygen atoms have a fourth bond to the hmp ligands, which presumably would render their involvement in a geminal coupling mechanism unfavorable. In a very recent study, Dismukes and coworkers suggested that O-O bond formation involving a [Co 4 O 4 ] 5+ -based "cubium" happens via geminal coupling of two terminal oxo ligands on the same Co center.…”
Section: Scheme 2 Oxo-oxo Coupling Pathwaymentioning
confidence: 99%
“…34 All three of these cubane WOC studies proposed catalytic pathways with different O-O bond formation steps: cross coupling of two oxo ligands 32 , nucleophilic attack by a water molecule 33 , and geminal coupling of an oxyl radical with a bridging oxygen. 34 Recently, however, it was suggested that Co(III) cubanes suffer from poor stability and that water oxidation catalytic activity is due to Co(II) impurities. 35 In light of these findings, the first Co(II)-based cubane WOC was reported in 2013 by Evangelisti et al 36 With the goal of mimicking the structure and functionality of the OEC of PS II, the complex [Co II 4 (hmp) 4 (μ-OAc) 2 (μ 2 -OAc) 2 (H 2 O) 2 ] (hmp=2-(hydroxymethyl)pyridine) (1) with two bridging and two monodentate acetate ligands as well as two water ligands was synthesized and found to be a stable homogeneous catalyst (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…So far RuO 2 and IrO 2 are the most effective catalysts for OER, but the high price and limited natural sources lead to search for alternative materials. The transition metal-based OER catalysts, especially cobalt-and nickel-containing oxide, hydroxide and oxyhydroxide, are reasonable selection due to their photocatalytic and electrocatalytic activity in OER, good stability and earth abundant nature [4][5][6][7][8][9][10][11][12][13][14]. A spinel-type cobalt oxide Co 3 O 4 , consisting of Co 2? at tetrahedral sites and Co 3? at octahedral sites, exhibits great electrocatalytic activity and stability in alkaline media [15,16].…”
Section: Introductionmentioning
confidence: 99%